Copyright and information service provision in public university libraries in Kenya. Issue 6 (13th August 2018) - Mathangani, Salome W.; Otike, Japheth
Abstract : Purpose: Copyright law supposedly brings a balance between copyright owners and information users as a way of creating a harmonious relationship. The purpose of this paper is to examine the relationship between Kenya's Copyright Act and the provision of information services in public university libraries in Kenya. Design/methodology/approach: The study was informed by both the organization theory and the social systems theory which, respectively, provided a base for discussion on the library and its basic functions, and an interdisciplinary approach that accommodate library services and law. Data were collected from a sample of 77 librarians from public universities libraries, and analyzed using the qualitative method. Findings: The study established that librarians were reasonably aware of the copyright Act. However, they were apprehensive and uncertain about copyright effect on the library. Evidence from the study showed that librarians needed to extend their knowledge and understanding of the copyright law for the effective provision of information services. The paper concludes that there is scope for librarians, using their wealth of knowledge and expertise, to make relevant and useful suggestions on copyright. Such contribution would assist in bringing harmony in the use of copyrighted materials. Originality/value: These findings are original and will be useful in giving general direction on copyright. The study highlights the important issue of universities as parent institutions providing needed leadership in the copyright area.